2017
DOI: 10.3382/ps/pew326
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evaluation of egg production curve in Thai native chickens by random regression and spline models

Abstract: The objective of this research is to investigate appropriate random regression models with various covariance functions, for the genetic evaluation of test-day egg production. Data included 7,884 monthly egg production records from 657 Thai native chickens (Pradu Hang Dam) that were obtained during the first to sixth generation and were born during 2007 to 2014 at the Research and Development Network Center for Animal Breeding (Native Chickens), Khon Kaen University. Average annual and monthly egg productions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 26 publications
5
11
1
1
Order By: Relevance
“…Previously reported heritability estimates for monthly egg production using random regression models in turkeys ranged from 0.08 to 0.12 [ 24 ]. In our study, estimates of heritability for weekly egg production were lower, ranging from 0.09 to 0.22, which is consistent with estimates obtained with spline models in laying hens [ 25 ]. For the first four weeks, our estimates of heritability for egg production were lower than those reported for White Leghorn hens and native chickens for the early weeks of production [ 22 ].…”
Section: Resultssupporting
confidence: 90%
“…Previously reported heritability estimates for monthly egg production using random regression models in turkeys ranged from 0.08 to 0.12 [ 24 ]. In our study, estimates of heritability for weekly egg production were lower, ranging from 0.09 to 0.22, which is consistent with estimates obtained with spline models in laying hens [ 25 ]. For the first four weeks, our estimates of heritability for egg production were lower than those reported for White Leghorn hens and native chickens for the early weeks of production [ 22 ].…”
Section: Resultssupporting
confidence: 90%
“…In the case of agro industry, the farming of different types of animal species has a number of waste eggshells after eggs are hatched. In Thailand, egg consumption has used significant amounts of egg that account for more than 15,000 million eggs a year 8 . From previous research, average weight of an egg is about 60 g, generating shell about 11%; thus, the produced wastes can be estimated as being around 90,000 tons per year 1 .…”
mentioning
confidence: 99%
“…Flock production rises sharply and reaches a peak 6–8 weeks later, followed by a gradual decline to about 65% after 12 months [ 1 ]. In Thai native chickens, our previous studies reported that the production peak occurred in the third month of the egg production period, after which, the monthly number of eggs decreased until the end of the production period [ 28 , 29 ]. Therefore, we inferred that the egg production performance was related not only to feeding management and environmental control [ 30 , 31 ] but also to follicular development.…”
Section: Discussionmentioning
confidence: 99%